PENDIDIKAN ETIKA BISNIS UNTUK MENINGKATKAN KESADARAN HIDUP BERWAWASAN LINGKUNGAN - Siti Maro'ah (UMSurabaya Publishing, 2008)
One of the most important social challenge for business is a balance between economic interests and maintain order terwjudkan ecologically sustainable development. Morals and ethics have a function to give the orientation of how and where we are heading in life, but the difference is that morality is a direct show of ways to go, while directing the choice of ethics precisely why you should move in suchaway? Business ethics is the application of ethical thinking in general, in business behavior. Business ethics is not a specific part of ethics which is different from ethics in general and are applicable only to business. If dishonesty is considered unethical and immoral, then anyone in business who are not honest with shareholders, employees, consumers or competitors, have acted in an unethical and immoral. According to the conventional ideology of economic development and preservation is a dichotomy that separated from one another. When in fact, both have a very close relationship and jointly become a national agenda that must be considered by the government and society in a country. This means that without an adequate environmental protection, development will be lost meaning (undermined). Thus the nature of the sustainable development, are the balance between economic interests with ecological sustainability (ecology are: Science of learning about how living creatures interact with one another within an ecosystem). Economic learning goals lead students to have the ability to solve the various problems it faces. Therefore, through the educational values in business ethics expected of students have the knowledge and the provision to be applied in everyday life which would not intentionally or engage in business activities. Kata kunci : Pendidikan Etika Bisnis, Kesadaran ramah lingkungan